2017
DOI: 10.3390/molecules22122126
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, Physiological and Transcriptomic Comparison between Burley and Flue-Cured Tobacco Seedlings in Relation to Carbohydrates and Nitrate Content

Abstract: Burley tobacco is a genotype of chloroplast-deficient mutant with accumulates high levels of tobacco-specific nitrosamines (TSNAs) which would induce malignant tumors in animals. Nitrate is a principle precursor of tobacco-specific nitrosamines. Nitrate content in burley tobacco was significantly higher than that in flue-cured tobacco. The present study investigated differences between the two tobacco types to explore the mechanisms of nitrate accumulation in burley tobacco. transcripts (3079) related to the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways analysis was achieved on KOBAS 3.0 [ 32 ]. R based on the hypergeometric distribution was operated to analyze not only GO terms but also KEGG pathways [ 33 ]. The calculation formula was as follows: (N represents the number of genes annotated in a pathway, n represents the number of DEGs in N, M represents the number of genes belonging to a particular pathway, and m represents the number of DEGs annotated in this particular pathway).…”
Section: Methodsmentioning
confidence: 99%
“…Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways analysis was achieved on KOBAS 3.0 [ 32 ]. R based on the hypergeometric distribution was operated to analyze not only GO terms but also KEGG pathways [ 33 ]. The calculation formula was as follows: (N represents the number of genes annotated in a pathway, n represents the number of DEGs in N, M represents the number of genes belonging to a particular pathway, and m represents the number of DEGs annotated in this particular pathway).…”
Section: Methodsmentioning
confidence: 99%
“…Burley is a mutant tobacco variety with characteristic yellow–green leaves. Although the genetic nature of this leaf phenotype remains unknown, it has been recently shown that key genes related to chlorophyll biosynthesis and photosynthesis are significantly down-regulated in burley plants and that this causes a decrease in chlorophyll content and a reduction of photosynthesis efficiency when compared to other tobacco varieties [24]. In previous studies, we have analyzed total protein extracts of other tobacco varieties (e.g., Petit Havana SR1) and of the model plant Arabidopsis exposed to oxidative stress and we did not observe any accumulation of covalently linked LSU dimer in total extracts [2532].…”
Section: Discussionmentioning
confidence: 99%
“…From our early study, we have found that nitrogen application was 5-folds higher in burley tobacco than in flue-cured tobacco to produce similar leaf biomass, and lower contents of pigment and energy substances and weaker nitrogen assimilation were the key factors contributing to nitrate accumulation in burley tobacco 7,8 . In this study, glycerol was applied to regulate carbohydrate and nitrate accumulation in two burley tobacco varieties.…”
Section: Introductionmentioning
confidence: 97%
“…In burley tobacco, high nitrate accumulation is correlated with nitrogen amount applied and reducing nitrogen level was effective in decreasing nitrate content 3 , although there is currently no in-depth coverage at molecular level in burley tobacco. From our early study, we have found that nitrogen application was 5-folds higher in burley tobacco than in flue-cured tobacco to produce similar leaf biomass, and lower contents of pigment and energy substances and weaker nitrogen assimilation were the key factors contributing to nitrate accumulation in burley tobacco 7 , 8 . In this study, glycerol was applied to regulate carbohydrate and nitrate accumulation in two burley tobacco varieties.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation